Penggunaan Media Sosial, EWOM, Intensi Pembelian dan Dampaknya terhadap Loyalitas Pengguna Scarlett Whitening di Jakarta - Indriyarti, Eko Retno (Journal of Business & Applied Management, 2023)
Social media's technological advancements now allow content to be presented in a more diverse format. These various formats then became one of the motivators for social media users to make more extensive purchases. In conjunction with products that are well-accepted by the general public, such as skin care products. Based on this, the purpose of this study is to investigate the determinants of Scarlett Whitening product loyalty by incorporating the variables of purchase intention, EWOM, and social media use. A total of 120 users of this product in Jakarta were analyzed using PLS-SEM and the SmartPLS 3.0 analysis tool. There are five hypotheses in this study, three of which have direct effects and two of which have indirect effects. This study explains why all the study's hypotheses are accepted. Purchase intent creates loyalty in this case. Meanwhile, the use of social media and EWOM drives purchase intent. In this study, purchase intention succeeded in mediating both the use of social media and loyalty, as well as the relationship between EWOM and loyalty. The positive use of social media and EWOM in the past has supported the reinforcement theory, which claims that the presence of purchase intention forms loyalty. The use of specific criteria, such as women who use new skin care products, can be used as input for future research.